Inextensible Flows of Tangent Developable Surfaces of Biharmonic Curves in SL2?(R) - Körp?nar, T.; Turhan, E. (Journal of Scientific Research, 2012)
We present some results on the inextensible flows of tangent developable surfaces of biharmonic curves in the . Finally, we find out explicit parametric equations tangent developable surfaces of biharmonic curves in the . Keywords: Biharmonic curve;Inextensible flows. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8987 J. Sci. Res. 4 (2), 365-371 (2012)